Regional aspects of the problem of restructuring use and ownership of agricultural land in the Republic of Ireland - O'Carroll, J.P.; Passchier, N.P.; Van der Wusten, H.H. (Economic & Social Studies, 1978)
This paper is an attempt to identify regional delineations which are relevant for the problem of restructuring the use and ownership of agricultural land in the Republic of Ireland. The social scientist's interest in regional classification arises from the fact that combinations of various dimensions of rural social structure are not randomly distributed spatially. The first aim is to identify regions which differ in regard to the structure of agriculture. Previous studies of farm structure have not used a systematic method for delineating regions. It was decided that a strict procedure be adopted rather than an impressionistic one. Subjectivity is seen as applying only to the selection of variables used for classification and to the degree of homogeneity within regions. The second aim is to relate the characteristics of each region to the problem of restructuring. The conformation of the elements, land, demography and economy characteristic of each region is seen as the context in which a restructuring programme must be considered. This paper (a) describes the nature of the data used; (b) examines the pattern of the combination of the basic dimensions of agriculture (i.e., land, demography, and production enterprise), which underlie regional variations: (c) compares a number of regional classifications based on different data sets and from these identifies stable core areas of the regions; and (d) examines the research and policy implications of the study. This approach differs from other classifications of rural areas in that it uses a rigorous procedure and is part of a larger research programme on the restructuring of agriculture for valid extrapolation of the findings of a number of community surveys on the problem of restructuring which were carried out in different parts of the country as part of the research programme. The broader implications of regional identification are discussed in the closing section.
Keywords: Agriculture - Ireland; Regional classification - Ireland